2011
DOI: 10.1039/c0cp01865a
|View full text |Cite
|
Sign up to set email alerts
|

Rotamer libraries of spin labelled cysteines for protein studies

Abstract: Studies of structure and dynamics of proteins using site-directed spin labelling rely on explicit modelling of spin label conformations. The large computational effort associated with such modelling with molecular dynamics (MD) simulations can be avoided by a rotamer library approach based on a coarse-grained representation of the conformational space of the spin label. We show here, that libraries of about 200 rotamers, obtained by iterative projection of a long MD trajectory of the free spin label onto a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
566
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 411 publications
(592 citation statements)
references
References 51 publications
25
566
1
Order By: Relevance
“…Distance distributions were simulated using a rotamer library approach (RLA) as implemented in MMM 15 . The rotamer library consists of 210 precalculated rotamers representing an ensemble of possible spinlabel side chain (R1) conformations at 175 K. The orientation of R1 introduced at the chosen residue with regard to the protein structure permits calculation of the energy for the R1-protein interaction in consideration of the LennardJones potential 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance distributions were simulated using a rotamer library approach (RLA) as implemented in MMM 15 . The rotamer library consists of 210 precalculated rotamers representing an ensemble of possible spinlabel side chain (R1) conformations at 175 K. The orientation of R1 introduced at the chosen residue with regard to the protein structure permits calculation of the energy for the R1-protein interaction in consideration of the LennardJones potential 26 .…”
Section: Methodsmentioning
confidence: 99%
“…We constructed two trimerization-domain mutants by replacing Thr166 (located in the cytoplasmic end of transmembrane helix 4) and Val176 (located in the cytoplasmic end of helix 5) with an MTSL-modified cysteine (R1). Simulations on the available crystal structures indicated that these spin labels are >1.8 nm apart and therefore suitable for DEER measurements 15 . We did not observe spectral broadening in the CW EPR measurements, which further supports the notion that the spin labels were >1.8 nm apart (Supplementary Fig.…”
Section: Design Of Epr Measurementsmentioning
confidence: 99%
“…DEER traces were recorded at Q band with all pulses set to 12 ns and frequency separation of 100 MHz (37). Data analysis and simulation of the MTSL rotamers on the X-ray structures were performed with the softwares DeerAnalysis2013 (38) and MMM2013.2 (19). The D-loop aspartates of TM287/288 and LmrCD were substituted by alanines using site-directed mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
“…1 B; Table S2). We applied in silico modeling of the internal conformational flexibility of the MTSSL using rotamer libraries obtained from different programs (47,53) to simulate distance distributions and intramolecular dipolar evolution functions to compare our results to the available x-ray structure. Comparison of the experimental distance distributions with predicted distributions based on the x-ray structure (19), using MMM in 298 K mode, shows that experimental and predicted mean distances are in good agreement (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The spin label (SL) utilized, MTSSL ((1-oxyl-2,2,5,5-tetramethylpyrroline-3-methyl) methanethiosulfonate)), possesses an intrinsic linker flexibility, which needs to be taken into account when a structure is refined or modeled based on PELDOR distance constraints. Several approaches to describe the intrinsic flexibility of the SL, such as rotamer libraries, as well as molecular dynamics (MD) simulations, have been introduced to enhance the reliability of structural modeling (46)(47)(48). We used site-directed spin labeling (SDSL) to investigate the relative orientation and conformational flexibility between POTRA domains of anaOmp85 by PELDOR spectroscopy using 27 double cysteine mutants including intra-and interdomain distance constraints.…”
Section: Introductionmentioning
confidence: 99%